Case 3669: Family-group names based on Ortalis Merrem, 1786 (Aves, Cracidae): proposed conservation of Ortalida-, Ortalis- or Ortalid- as the stem and suppression of family-group names based on Ortalis Fallén, 1810 (Insecta, Diptera) in the latter two instances, and acceptance of the English text of part of Article 29.3.3 of the Code as definitive in the second instance. - Donegan, Thomas M (Bulletin of Zoological Nomenclature, 2015)
The Case is brought under Articles 78.1, 81.1 and 89 of the Code to resolve a controversy surrounding the stem of family-group names based on Ortalis Merrem, 1786, a genus of large, pheasant-like birds (chachalacas) of the New World. This genus has a junior homonym in Diptera, Ortalis Fallén, 1810, and various family-group names based on the dipteran genus were proposed before anyone noticed the homonymy. Despite their invalidity under Article 39 of the Code, these dipteran names remain available names, preoccupying obvious stems for avian family-group names. A new tribe Ortalidaini Donegan, 2012 was proposed for the avian Ortalis, its non-standard stem Ortalida- being chosen under Article 29.6 of the Code to avoid homonymy with dipteran names. Subsequently, an attempt was made to emend Ortalidaini to Ortalisini David, 2014, but the emended name is identical in spelling to the available dipteran name Ortalisini Acloque, 1897. Acceptance of Ortalidaini as the valid spelling might be threatened as a result of the differing English and French versions of Article 29.3.3 of the Code concerning family-name stem formation, the French preventing an otherwise valid emendation of this name, but the English not. The Commission is asked to choose between (i) endorsing Ortalidaini Donegan, 2012 as being based on an ‘appropriate’ stem under Article 29.6; or (ii) using its plenary power to suppress Ortalisini Acloque 1897 in favour of David (2014)‘s junior homonym Ortalisini, giving precedence to the English version of Article 29.3.3 of the Code and deeming David (2014)’s emendation to be valid on different grounds to those stated (i.e. Ortalidaini being inappropriate under Article 29.6); or (iii) suppressing all competing family-group names based on Ortalis Fallén, 1810 and making the ‘standard’ family-group name Ortalidini thereby capable of usage in Aves.
Keywords: ceroxydidae; chachalacas; correct original spelling; English-French discrepancy; family-group names; homonymy; Nomenclature; ortalidaini; ortalidini; ortalini; ortaliscidae; ortalisini; stem formation; taxonomy